Monitoring, analysis, and correction of magnetic field fluctuations in echo planar imaging time series. Issue 2 (14th August 2014) - Kasper, Lars; Bollmann, Saskia; Vannesjo, S. Johanna; Gross, Simon; Haeberlin, Maximilian; Dietrich, Benjamin E.; Pruessmann, Klaas P.
<x xml:space="preserve">Abstract</x> Purpose To assess the utility of concurrent magnetic field monitoring for observing and correcting for variations in k‐space trajectories and global background fields that occur in single‐shot echo planar imaging (EPI) time series as typically used in functional MRI (fMRI). Methods Field monitoring was performed using an array of NMR field probes operated concurrently with series of single‐shot EPI acquisitions from a static phantom. The observed fluctuations in field evolution were analyzed in terms of their temporal and spatial behavior at the field level as well as at the level of reconstructed image series. The potential to correct for such fluctuations was assessed by accounting for them upon image reconstruction. An indication of the number and relative magnitude of underlying effects was obtained via principal component analysis. Results Trajectory and global field variations were found to induce substantial image fluctuations. Global field fluctuations induced standard deviations in image intensity up to 31%. Fluctuations in the trajectory induced ghosting artifacts with standard deviations up to 2%. Concurrent magnetic field monitoring reduced the fluctuations in the EPI time series to a maximum of 1.2%. Conclusion Concurrent magnetic field monitoring holds the potential to improve the net sensitivity of fMRI by reducing signal fluctuations unrelated to brain activity. Magn Reson Med 74:396–409, 2015. © 2014 Wiley Periodicals, Inc.